2023
DOI: 10.1007/s10648-023-09785-7
|View full text |Cite
|
Sign up to set email alerts
|

Integration in the Achievement Motivation Literature and the Hierarchical Model of Achievement Motivation

Abstract: Integration is a valuable yet underutilized process in scientific literatures, including the achievement motivation literature. In this piece, we advocate for and illustrate the benefits of giving integration a central place within the achievement motivation literature. We pay particular attention to the hierarchical model of achievement motivation that is explicitly and intensively integrative in nature. We believe that this hierarchical model may be used as a theoretical foundation from which to organize and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 232 publications
0
10
0
Order By: Relevance
“…Among the different achievement goals, mastery‐approach goals are regarded as the most adaptive. Students who endorse mastery‐approach goals accrue a highly positive set of outcomes, including higher levels of academic achievement, perceived competence and intrinsic motivation (Elliot & Thrash, 2001; Huang, 2011, 2016; Hulleman et al., 2010).…”
Section: Achievement Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the different achievement goals, mastery‐approach goals are regarded as the most adaptive. Students who endorse mastery‐approach goals accrue a highly positive set of outcomes, including higher levels of academic achievement, perceived competence and intrinsic motivation (Elliot & Thrash, 2001; Huang, 2011, 2016; Hulleman et al., 2010).…”
Section: Achievement Goalsmentioning
confidence: 99%
“…Achievement goals pertain to ‘aims that focus on competence’ (Elliot & Murayama, 2008, p. 614). They create a framework through which individuals construe experience and invest themselves in achievement‐relevant situations (Elliot & Thrash, 2001). One of the core ideas of the achievement goal approach to achievement motivation is that goals can be distinguished in terms of how students define competence.…”
Section: Achievement Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is overlap across the main ideas of situated expectancy-value theory, social–cognitive career theory, and many specific perspectives in social psychology around goals and values. There have been important theoretical integration attempts, mostly in social psychology, to synthesize perspectives on motivation and decision making and create broad theories (e.g., Ajzen & Kruglanski, 2019; Dweck, 2017; Elliot & Sommet, 2023; Kruglanski et al, 2014). Integrating the organizational psychology literature into this work and applying it to the career context is an important future direction.…”
Section: Future Research Implications: Moving Outside Of Our Siloesmentioning
confidence: 99%
“…These students may work hard to focus on their performance to avoid failing, although they tend to have negative attitudes toward learning (Busato et al, 2000;Conroy & Elliot, 2004). In contrast, extensive research has shown that mastery-oriented goals are associated with more positive attitudes toward learning and adaptive learning strategies (Elliot & Sommet, 2023;Finney et al, 2004;Harackiewicz et al, 2002).…”
Section: Mg and Fof In Learning And Well-beingmentioning
confidence: 99%